2021
DOI: 10.1111/sed.12860
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional submerged wall jets and their transition to density flows: Morphodynamics and implications for the depositional record

Abstract: Jets that expand from an orifice into an ambient water body represent a basic flow model for depositional environments related to expanding flows. Momentum-dominated jets evolve into gravity-dominated density flows. To understand this transition and its sedimentological relevance, three-dimensional tank experiments with submerged wall jets were conducted, systematically varying parameters such as the initial density difference, bed slope, grain size and sediment supply. Bedform successions could be subdivided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The sediment built a channel extending beyond the fixed channel, and this widened over a distance of a metre from ~20 cm (the fixed channel width) to ~36 cm; this channel was filled with antidunes. Downstream of this widening constructional channel mouth is a lobe similarly covered in antidunes in proximal areas, and asymmetrical inphase bedforms in distal parts, interpreted as supercritical dunes (Fedele et al, 2016;Lang et al, 2021). Lang et al ( 2021) used a 3component velocity measurement technique, and observed no lowering of the velocity maximum, even though the flow expanded laterally by ~8.9 °in the initial metre, and presumably continued with a similar expansion rate.…”
Section: Flows Across Continuous Slopes Without Hydraulic Jumpsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sediment built a channel extending beyond the fixed channel, and this widened over a distance of a metre from ~20 cm (the fixed channel width) to ~36 cm; this channel was filled with antidunes. Downstream of this widening constructional channel mouth is a lobe similarly covered in antidunes in proximal areas, and asymmetrical inphase bedforms in distal parts, interpreted as supercritical dunes (Fedele et al, 2016;Lang et al, 2021). Lang et al ( 2021) used a 3component velocity measurement technique, and observed no lowering of the velocity maximum, even though the flow expanded laterally by ~8.9 °in the initial metre, and presumably continued with a similar expansion rate.…”
Section: Flows Across Continuous Slopes Without Hydraulic Jumpsmentioning
confidence: 99%
“…Process studies on channel mouth settings have been predominantly undertaken using physical modelling (e.g., Pohl et al, 2019;Spychala et al, 2020;Lang et al, 2021). In addition, there is a broader body of experimental work on density flows crossing slope breaks (e.g., García and Parker, 1989;García, 1993;Gray et al, 2005;Gray et al, 2006;Pohl et al, 2020), which can provide insights into channel mouth processes.…”
Section: Insights From Physical Experiments Numerical Simulations And...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the Las Lajas block‐and‐ash flow waxed and the aggrading deposits gradually filled the alluvial channel, it increasingly spilled out, splaying laterally across the golf course and, 2 km downcurrent of this, overtopped interfluves into local drainages, most notably on the outside of a marked bend where, as flow conditions waxed, a significant stripped part of the current escaped southwards into a minor catchment (Figure 3) where it partially buried and then battered the village of San Miguel. Where this flow‐stripping and overflow event occurred, there is evidence for marked erosional scour, as in crevasse‐splay events of turbidity currents (Lang et al., 2021; Piper et al., 2007). Where the current overtopped the interfluve, standing trees were felled and soil was eroded, leaving longitudinal furrows and partly excavated large alluvial boulders with stoss‐side crescent‐scours and lee‐side gravel tails (Figure 3c; Allen, 1984).…”
Section: Discussionmentioning
confidence: 99%